A tale of paper and gold: The material history of money in South Africa. Issue 2 (4th May 2021) - Feingold, Ellen; Fourie, Johan; Gardner, Leigh
ABSTRACT: This paper uses the South African objects in the National Numismatic Collection of the Smithsonian to tell a new material history of money in South Africa. In other parts of the continent, research about the currencies in use and how these changed over time have offered a new perspective on the impact of colonialism, commercialization, and the rise of state capacity. South Africa, and southern Africa more generally, has remained on the periphery of these debates. This paper begins to fill this gap. It shows that even in Africa's most financially developed region, the process of establishing a stable national currency was long and halting, reflecting struggles over South Africa's relationship with the global economy and the rise and fall of apartheid.